Simulation of PEM fuel cell integrated DVR using SRF-ANFIS controller for power quality enhancement - Bhavani, R.; Praba, Rathina; Ananthakumaran, S. (Maǧallaẗ al-abḥath al-handasiyyaẗ, 2021)
Voltage related Power Quality (PQ) problems are the attracting eye of researchers causes huge loss in productivity and profitability for both utilities and consumers. Dynamic Voltage Restorer (DVR) is a well known custom power device provides an economical solution for the alleviation of power quality problems. Generally, battery energy storage is used as an input for DVR but batteries are still bulky, costly and must be disposed of once their chemicals are used up which limits the compensation capability of DVR. Now- a-days, Fuel Cell (FC) technologies have become more attention owing to their high efficiencies and low emissions. This project aims to model and simulate Proton Exchange Membrane Fuel Cell (PEMFC) and is used as a DC input source for DVR. The suitable boost converter is designed and modelled to lift up the fuel cell output voltage suitable as DC link voltage for DVR. Adaptive Neuro Fuzzy Inference System (ANFIS) controller uses Synchronous Reference Frame Theory (SRF) algorithm to generate d and q axis components of reference signal for Voltage Source Converter (VSC) of DVR. This PEMFC DVR is verified for balance and unbalanced voltage sag, swell and harmonics using MATLAB/SIMULINK. A simulation result proves that this PEMFC DVR is capable to provide a technically advanced and economic solution for balanced, unbalanced voltage sag and swell. During compensation, the DVR DC input voltage is also preserved as constant which enhances the compensation capability of DVR